Formulating a Digital Marketing Strategy as a Solution for Disseminating Sharia Financial Literacy at Sharia Pawnshops - Ash Shiddiqi, M. Zidan Fahmi (Maliki Interdisciplinary Journal, 2025)
This study aims to formulate an effective digital marketing strategy as a solution for expanding Islamic financial literacy through the role of Pegadaian Syariah. Using a qualitative descriptive approach based on literature review, the research analyzes educational digital marketing trends and their implementation in enhancing public awareness and trust toward Islamic financial services. The findings indicate that an educate–engage–enable digital marketing strategy can improve public understanding and participation. Educational content presented in visual, interactive, and contextual forms strengthens brand awareness, trust, and promotes Islamic financial inclusion. The study recommends implementing modular content, A/B testing, collaborations with value-driven micro-influencers, and learning outcome assessments to optimize the long-term impact of digital Islamic financial literacy.